EFEKTIVITAS QUESTION STUDENT HAVE TERHADAP KEAKTIFAN BELAJAR PAI - nalita azzura; Heru Juabdin Sada; Erni Yusnita; Syaiful Anwar; Zahra Rahmatika (Jurnal Bilqolam Pendidikan Islam, 2025)
This study aims to evaluate the effectiveness of the Question Student Have (QSH) method in enhancing students’ learning activeness in Islamic Religious Education (PAI) at SMK Negeri 7 Bandar Lampung, with a particular focus on student engagement in problem-solving activities. The research employed a quantitative approach with a quasi-experimental posttest-only control group design, involving class XI FM 2 as the experimental group and XI FM 3 as the control group. The instrument, a learning activeness questionnaire, was validated and found to be reliable, with a Cronbach’s Alpha of 0.858. Results from the independent sample t-test revealed a significance value of 0.012 (< 0.05), indicating a significant difference between the QSH class and the conventional learning class. These findings suggest that QSH can enhance students’ participation in problem-solving through an anonymous mechanism, thereby reducing feelings of embarrassment and fear of making mistakes. The novelty of this study lies in the application of QSH in the context of vocational education, implying that this method contributes to the development of students’ activeness, critical thinking, communication skills, and collaboration.